A Novel Designed Valved Conduit for RVOT Reconstruction in Grown-up Congenital Heart Patients: a Glimpse Down the Road - Liebrich, Markus; Hemmer, Wolfgang; Uhlemann, Frank; Merz, Constanze; Voth, Wladimir; Scheid, Michael; Tzanavaros, Ioannis (The Thoracic and Cardiovascular Surgeon, 2016)
Background A plethora of valves and valve conduits are available for reconstruction of the right ventricular outflow tract (RVOT) for grown-up congenital heart patients. However, for several reasons, the ideal pulmonary valve substitute still remains the subject of debate. In this study, we investigated the preliminary clinical and echocardiographic results after implantation of the RVOT Elan (Vascutek, Renfrewshire, United Kingdom) conduit in adolescents and adults.Material and Methods Between October 2012 and December 2014, a total of 27 patients (19 males, mean age: 23.7 ± 22.5; range: 9–74 years) received a RVOT Elan conduit for RVOT reconstruction and were prospectively followed up clinically and echocardiographically. Twenty-five patients had previous cardiac surgery. The median number of prior operations per patient was 2 (range: 1–4). Tetralogy of Fallot was the most common diagnosis (n = 7).Results At a mean follow-up time of 0.9 ± 0.61 years (100% complete), all patients (27 of 27) were alive and in New York Heart Association Class I. Adverse events defined as valve failure, thrombosis, embolism, bleeding, or endocarditis did not occur. Freedom from reoperation in general was 100%. At 1-year follow-up, median peak pressure gradients (Δ Pmax) across the RVOT Elan conduit were 15 ± 3.2; 15.3 ± 2.1Δ, 16 ± 4.8, and 16.3 ± 5.1 mm Hg for the 19 (n = 3), 21 (n = 3), 23 (n = 6), and 25 mm (n = 15) conduit size, respectively.Conclusion The RVOT Elan conduit revealed excellent preliminary clinical and hemodynamic performances independent from the underlying cardiac pathology with insignificant transvalvular gradients and nonturbulent flow characteristics.
Keywords: congenital heart disease; reoperation; pulmonary valve